2013
DOI: 10.2174/18715273113126660177
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Inhibitors of Microglia to Reduce Neuroinflammation

Abstract: Many of the non-toxic compounds identified in this screen as inhibitors of microglia, including spironolactone, may be explored as viable therapeutic options in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We previously screened a 1040 drug library for their capacity to enhance TNF-α production in lipopolysaccharide (LPS)-exposed adult human microglia and identified niacin (nicotinic acid, vitamin B3), meclocycline, bumetanide and orlistat with this effect [44]. Here, we used macrophages since they are a major phagocytic population in many neurological lesions [32], and can be purified easily from the bone marrow of young (2-3 months) and middle-aged (9-12 months) mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously screened a 1040 drug library for their capacity to enhance TNF-α production in lipopolysaccharide (LPS)-exposed adult human microglia and identified niacin (nicotinic acid, vitamin B3), meclocycline, bumetanide and orlistat with this effect [44]. Here, we used macrophages since they are a major phagocytic population in many neurological lesions [32], and can be purified easily from the bone marrow of young (2-3 months) and middle-aged (9-12 months) mice.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we confirmed these results using the lysolecithin model in young and middle-aged mice and examined whether remyelination could be enhanced by pharmacological stimulation of aging macrophages/microglia. We screened 1040 mostly generic medications from the NINDS Custom Collection II database for compounds that altered tumor necrosis factor-α secretion from activated human microglia [44]. From this screen, we discovered niacin, or vitamin B3, to be effective in stimulating tumor necrosis factor-α from human microglia.…”
Section: Discussionmentioning
confidence: 99%
“…While we identified meclocycline as an activator of microglia (33), it was necessary to confirm that its better tolerated derivative, demeclocycline, also has such activity. We first carried out some preliminary studies with mouse bone marrow derived macrophages (BMDM).…”
Section: Demeclocycline Promotes the Activity Of Monocytes And Macropmentioning
confidence: 99%
“…We discovered the pro-activation capacity of amphotericin B on microglia during a screen of a 1,040-drug library (33). During that screen, we discovered another stimulator of the activity of microglia in culture, as measured by TNF-α production: meclocycline, a tetracycline antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…As aged microglia produce more proinflammatory cytokines than young ones during stroke, drugs that penetrate into the CNS to inhibit microglia, such as minocycline or laquinimod, might be beneficial in tempering the excessive proinflammatory response . These drugs may partially impede the beneficial effects of microglia, such as positive phagocytosis, but therapy that preferentially enhances phagocytosis and chemotaxis is also effective. For instance, monophosphoryl lipid A modified from lipopolysaccharide is an agent that mainly stimulates TIR‐domain‐containing adapter‐inducing interferon‐β, but not the proinflammatory myeloid differentiation factor 88 pathway downstream of Toll‐like receptor (TLR4), and its effect has been proven to increase the microglial phagocytosis of amyloid‐β in Alzheimer's disease mouse model and improve clinical outcomes .…”
Section: Aging Microglia and Relevant Interventions For Strokementioning
confidence: 99%